Ozone Trends during 1979–2019 over Tibetan Plateau Derived from Satellite Observations - Zou, Mingmin; Xiong, Xiaozhen; Wu, Zhaohua; Yu, Chao (Frontiers in Earth Science, 2020)
Ozone (O3) is a very important atmospheric component related to many atmospheric processes. The Tibetan Plateau (TP) has played an important role to weather and climate in South Asia and was found to modulate the variation of ozone amount, leading to a low-ozone event over the TP in both summer and winter. To better understand the changing trend of ozone, a novel statistic method, that is, the ensemble empirical mode decomposition method, is used to analyze the trends of total column O3 (TCO) and the ozone deficit after removing the corresponding zonal mean of TCO over the TP. Data of TCO over the TP from satellite observations by Ozone Monitoring Instrument/Aura from 2004 to 2019 and Ozone Mapping and Profiler Suite/S-NPP from 2013 to 2019 are used, and, for comparison, the long-term merged ozone data from NASA are used to analyze the trend of TCO in three latitude zones of 25°N–30°N, 30°N–35°N, and 35°N–40°N near the TP. In consistent with some other studies, a slight recovery of ozone around 1996–1997 is evident, with the peak occurring in 2000, but the rate is near zero in 2005. The mean annual trends over 30°N–35°N are −0.836 ± 0.233 DU/yr during 1979–1996 and 0.021 ± 0.124 DU/yr during 1997–2018. Based on the Ozone Monitoring Instrument data, TCO over the TP [27.5°N–37.5°N, 75.5°E–105.5°E] shows a consistent increase trend from 2005 to 2019, and the ozone deficit starts to increase since 2009, indicating that the ozone increase rate over TP is larger than the zonal average. The ozone deficit over the TP shows an even more rapid increase trend after 2015, with a larger increase during winter than summer. Further analysis of the low-ozone event in winter and early summer (MJJ) from 2004 to 2019 shows that the low-ozone event in May is much deeper than that in winter and also lasts longer than that in February. This study confirms the mechanism of the winter low-ozone event over the TP is more complex than that in summer. This finding of more and faster increase in ozone over the TP relative to the zonal mean suggests the possibility of the decrease in the ultraviolet radiation over the TP, which will benefit human skin health and biosphere over the TP; therefore, it is important to continue to monitor the ozone trend and study its mechanism.